Enable digital transformation: entrepreneurial leadership, ambidextrous learning and organisational performance. Issue 12 (2nd December 2021) - Wu, Ting; Chen, Beibei; Shao, Yixuan; Lu, Hongxu
ABSTRACT: Although digital transformation (DT) is gaining importance, we know little about the challenge of ambidextrous learning in that context or how to manage the challenge. To address this gap, this study explores the relationships among entrepreneurial leadership, ambidextrous learning, and organisational performance in DT, and the influence of non-technical digital context (i.e. change in operation) on these relationships. Using multi-source data from a sample of 73 CEOs/entrepreneurs and 377 middle managers in China, we find that in DT: (1) ambidextrous learning is positively related to organisational performance; (2) entrepreneurial leadership has a positive impact on ambidextrous learning; (3) ambidextrous learning mediates the relationship between entrepreneurial leadership and organisational performance. Our results further reveal that change in operation strengthens the effect of ambidextrous learning on organisational performance while it has no significant impact on the relationship between entrepreneurial leadership and ambidextrous learning. Finally, we discuss how our ﬁndings extend the studies of entrepreneurial leadership and ambidextrous learning and provide implications for DT practices.